Association of MTHFR (C677T and A1298C) Gene Variants Polymorphisms with Migraineurs: A Case-control Study - Somavarapu Thomas, Anne Sahithi; Saraswathy, Radha; Thayanithy, Muthu (Applied Science and Engineering Progress, 2022)
In recent years, the activity of the regulatory enzyme 5,10-methylenetetrahydrofolate reductase (MTHFR), which influences migraine attacks, has been intensely discussed. In particular, this genetic risk factor, together with diagnostic and symptomatic characteristics, can predispose to Migraine. The present study assessed the functional polymorphism and its prevalence of MTHFR (C677T and A1298C) gene variants among 186 Migraineurs (116 (MA) and 70 (MWA)) compared with 152 healthy individuals. The incidence of (MTHFR 677 T and MTHFR 1298C) allele were significantly higher in Migraineurs (30.6%, 51.3%). Genotypes T677T and C1298C have been associated to induce migraine attacks (Odds Ratio (OR) = 3.53; 95% Confidence Interval (CI) = 1.18–27.86; p-value = 0.01) and (OR = 7.19; 95%, CI = 0.19–27.41; p = 0.01) respectively. Similarly, mutant interaction analysis was performed, and it was found that both genotypes were more closely associated with Migraine. Interactions of both variants had a higher risk for causing migraine in the genotypes CCAA (p = 0.02), CCCC (p = 0.05), CTAA (p = 0.03), and TTAC (p = 0.02). Patients having MA are more susceptible to genotypes (CCAA, CTAA, and TTAC), while MWA was more affected by (CCCC p = 0.05). Altogether, it could be concluded that folate metabolism plays an essential role in the onset of Migraine. Further studies involving larger populations may pave the way to clarify genotype-phenotype relationships.